Effect of two corticotomy protocols on periodontal tissue and orthodontic movement - Zuppardo, Marcelo Lelis [UNESP]; Santamaria, Milton; Ferreira, Camila Lopes [UNESP]; Longo, Mariéllen [UNESP]; Cirelli, Joni Augusto [UNESP]; Santamaria, Mauro Pedrine [UNESP]; Jardini, Maria Aparecida Neves [UNESP] (FapUNIFESP (SciELO), 2020)
Objective: To compare two corticotomy surgical protocols in rats to verify whether they alter conventional orthodontic movement. Methodology: Sixty Wistar rats were divided into three groups – orthodontic movement (CG), orthodontic movement and corticotomy (G1) and orthodontic movement with corticotomy and decortication (G2) – and euthanized after 7 and 14 days. Tooth movement (mm), bone volume fraction and bone volume ratio to total volume (BV/TV), and bone mineral density (BMD) were evaluated by micro-CT. The total amount of bone was measured in square millimeters and expressed as the percentage of bone area in the histomorphometry. The number of positive TRAP cells and RANK/RANKL/OPG interaction were also investigated. Results: Day 14 showed a statistically significant difference in orthodontic tooth movement in CG compared with G1 (7.52 mm; p=0.009) and G2 (7.36 mm; p=0.016). A micro-CT analysis revealed a difference between CG, G1 and G2 regarding BV/TV, with G1 and G2 presenting a lower BV/TV ratio at 14 days (0.77 and 0.73 respectively); we found no statistically significant differences regarding BMD. There was a difference in the total amount of bone in the CG group between 7 and 14 days. At 14 days, CG presented a significantly higher bone percentage than G1 and G2. Regarding TRAP, G2 had more positive cells at 7 and 14 days compared with CG and G1. Conclusion: Corticotomy accelerates orthodontic movement. Decortication does not improve corticotomy efficiency.
Keywords: Animal study; Corticotomy; Orthodontic movement